Mesotelioma della pleura nella provincia di Trieste / Mesothelioma of the pleura in the Province of Trieste - Bianchi, C.; Bianchi, T.; Tommasi, et al., M. (La Medicina del Lavoro, 2007)
La Provincia di Trieste (popolazione di circa 240.000 abitanti) presenta un’elevata incidenza di mesotelioma maligno della pleura. Il presente studio è stato condotto per raccogliere dati preliminari sull’attuale evoluzione dell’epidemia in questa area negli ultimi anni e determinare le caratteristiche dell’esposizione all’asbesto nei casi esaminati. Sono stati rivisti i casi di mesotelioma della pleura diagnosticati presso la Sezione di Chirurgia Toracica dell’Università di Trieste nel periodo gennaio 2001-maggio 2006. La diagnosi istologica era generalmente basata su materiale ottenuto in corso di toracoscopia, pleurectomia e pleuropneumonectomia. In tre casi la diagnosi patologica fu fatta con biopsia della parete toracica e in altri tre casi attraverso esame citologico del liquido pleurico. Una dettagliata storia professionale fu ottenuta dai pazienti stessi al momento del primo ricovero. Il gruppo comprendeva 89 uomini e 10 donne di età variante da 43 a 89 anni. Sulla base dei dati anamnestici 95 casi vennero classificati come asbesto-correlati. La maggioranza dei pazienti aveva lavorato nel settore navale: 46 casi nei cantieri navali, 13 casi nel porto e 8 casi come marittimi. Tredici pazienti avevano lavorato in varie industrie (siderurgica, petrolchimica, ecc.). Un’ampia gamma di occupazioni compariva nella storia di altri 14 pazienti (manutentore di ascensori, pasticciere, proiezionista di cinema, tecnico delle linee telefoniche, vigile del fuoco, ecc.). Cinque donne erano state esposte all’asbesto in ambiente domestico. In circa il 70% dei casi l’esposizione all’asbesto era iniziata prima del 1960 e in 2/3 dei casi era durata per 20 anni o più. I periodi di latenza intercorsi fra prima esposizione e diagnosi del tumore variavano tra 25 e 71 anni (media 49,3, mediana 49,0). Una paziente aveva subito un’irradiazione toracica per malattia di Hodgkin. L’epidemia di mesotelioma nella Provincia di Trieste non presenta segni di attenuazione. Accanto ai lavori navali, svariate altre occupazioni appaiono associate al tumore in questa area. Mesothelioma of the pleura in the Province of Trieste Background: The Province of Trieste, north-eastern Italy (population about 240,000), has been identified as an area with a high incidence of pleural mesothelioma. Objectives: i) To obtain preliminary data on the trend of the mesothelioma epidemic in the Province of Trieste during the last six years; ii) to define the cases in terms of asbestos exposure. Methods: Pleural mesotheliomas diagnosed at the Department of Surgery, Thoracic Surgery Unit, Trieste University, in the period January 2001-May 2006 were reviewed. The histological diagnosis was generally based on material obtained at thoracoscopy, pleurectomy, or pleuropneumonectomy. In three cases the pathological diagnosis was made by biopsy of the thoracic wall, and in a further three cases by cytological examination of pleural fluid. Detailed occupational histories were obtained from the patients themselves at the time of first admission. Results: The group included 99 people resident in the Province of Trieste (89 men and 10 women, aged between 43 and 89 years). On the basis of the occupational history, 95 cases were defined as asbestos-related. A majority of patients had been employed in marine work, including shipbuilding (46 cases), port activity (13 cases), and maritime trades (8 cases). Thirteen patients had worked in other industries (iron industry, petrochemical, etc.). Fourteen people had been employed in a variety of occupations (fire-fighter, lift mechanic, cinema projectionist, pastry worker, telephone technician, etc.). Five women had histories of exposure to asbestos at home. About 70% of the patients had their first exposure to asbestos before 1960. Two-thirds of the cases were exposed to asbestos for 20 years or more. Latency periods (time intervals elapsed between first exposure to asbestos and diagnosis of mesothelioma) ranged from 25 to 71 years (mean 49.3, median 49.0). One patient had a history of prior thoracic irradiation for Hodgkin’s disease. Conclusions: In the Province of Trieste the mesothelioma epidemic does not show any signs of abatement. Besides marine work, a variety of other occupations appear to be associated with the tumour in this area.